To lead or not not to lead? Identifying athlete leadership roles in sport teams - Fransen, K.; Vanbeselaere, N.; vande Broek, G.; de Cuyper, B.; Boen, F. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Research in sport leadership has mainly focused on the leadership of the coach. However, players within the team can also occupy leadership roles and become crucial for an optimal team functioning. The few studies that did examine the different roles of athlete leaders have distinguished between three leadership roles; task leader, social leader, and external leader (Loughead, Hardy, & Eys, 2006). However, these athlete leadership roles and their characteristics have not yet been thoroughly elaborated. Further investigation in this emerging area is needed considering the possible overlap between the different leadership roles as well as their relative influence on team outcomes. Aims: In this study, we want to extend the current research knowledge on two points. First, we want to extend the previous categorization of leadership roles by exploring the existence of an additional leadership role, namely the motivational leader on the field. In our opinion, consideration of this motivational role can enhance our understanding of the complex nature of athlete leadership. In this study, the occurrence of the four athlete leadership roles within sport teams will be tested. We predict that the team captain overlaps with the social leader at the recreational level, but with the task leader at the highest performance level. In addition, we assume that the influence of the team captain is overrated and that other players within the team will occupy equally important leadership roles. Second, we will examine athlete leadership in a broader framework. In analogy with models of coach leadership, we will evaluate the qualities of the four leader roles on three domains: (a) personal characteristics (e.g. experience, competence), (b) behaviours (e.g. communicating, encouraging) and (c) athlete outcomes (e.g. collective efficacy). In particular, we expect that the motivational leader has the strongest influence on the collective efficacy beliefs of his/her teammates. Method: The database of the Flemish Trainer School`s (VTS) was used to contact 4500 qualified coaches of all the different team sports in Flanders (Belgium). These coaches were also asked to motivate their players to participate by referring them to the player-specific on-line version of the questionnaire. Data collection will be finished by March 2012, after which the data will be analyzed by correlational and regression analyses. Discussion: Good athlete leaders are crucial for an optimal team functioning. Knowledge about athlete leaders` characteristics and the different roles that they occupy can be used to identify and guide athlete leaders in a sport team.